Microwave-assisted telescoped cross metathesis-ring closing aza-Michael reaction sequence: step-economical access to nicotine–lobeline hybrid analogues. Issue 117 (11th November 2015) - Drège, E.; Oko, J.; Venot, P.-E.; Gigant, N.; Joseph, D.
Abstract : Step-economical access to nicotinic acetylcholine receptor ligands hybrids through an efficient telescoped cross-metathesis/cyclizing aza-Michael addition involving N-heteroaromatic olefinic derivatives. Abstract : A series of 2, 5-disubstituted pyrrolidines was synthesized through an efficient telescoped cross-metathesis/cyclizing aza-Michael addition involving N-heteroaromatic olefinic derivatives. This synthetic route was applied to the preparation of original nicotine–lobeline, nicotine–pelletierine and lobeline–nicotine–epibatidine hybrids.